Studi Gender: Partisipasi Publik dan Penguatan Individu Rumah Tangga - Yusriani, Eni Ria; Qistina, Selamah Rabia (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2023)
The conservative paradigm prevalent in society perceives the role of women as suboptimal both in domestic life and in the public sphere. Therefore, this research aims to thoroughly examine the contributions of women in household and societal contexts. The research is conducted in the form of a literature review. Data is gathered from 40 research journals using keywords such as gender, public policy, household, and Islamic values. The data is then processed using data reduction to generate a comparative analytical model. The research findings indicate that the contributions of women in domestic life can be observed through the formation of character values in children. Character values are categorized into terminal and instrumental values. On the other hand, in the public sphere, when facilitated by the government or supported by the family, women are able to contribute to economic strengthening and other social movements. The indication towards these categories of women's values is based on Islamic ethics, which states that women have equal value and position as men. The findings also determine the